Association between lifestyle behaviors and body mass index with blood pressure classifications among older adults with hypertension in China - Jian Wu; Yue Chen; Yudong Miao; Quanman Li; Clifford Silver Tarimo; Clifford Silver Tarimo; Nengguang Dai; Qiuping Zhao; Yadong Niu (Frontiers in Public Health)
ObjectiveThis study aimed to examine the association between lifestyle behaviors and body mass index (BMI) along with their potential interactions with the severity of blood pressure (BP) classifications among older adults with hypertension.MethodsAmong 17,441 participants, lifestyle behaviors were assessed, including smoking, drinking, dietary patterns, physical activity, and sleeping. Multinomial logistic regression was used to examine the association between lifestyle behaviors and BMI with BP classifications, and multiplicative interactions were included to estimate potential interactions. To explore variations, analyses were also stratified by BMI.ResultsHigh-risk dietary pattern and obesity were negatively associated with lower BP classifications, with odds ratios (ORs) and 95% confidence intervals (CIs) for normal BP, high-normal BP, and grade 1 hypertension in high-risk dietary pattern were 0.74 (0.57–0.95), 0.69 (0.54–0.90), 0.75 (0.59–0.95), and the ORs (95% CIs) in obesity were 0.61 (0.53–0.69), 0.77 (0.67–0.89), 0.82 (0.73–0.93). Compared with never drinking, former drinkers had higher odds of having normal BP (OR: 1.45, 95% CI: 1.15–1.82), high-normal BP (OR: 1.31, 95% CI: 1.02–1.67), and grade 1 hypertension (OR: 1.26, 95% CI: 1.01–1.58). The multiplicative interaction between drinking status and BMI was found on BP classifications (Pforinteraction <0.05), and the effects of former drinking and low PA level on BP control were significant in overweight and underweight groups, respectively (P < 0.05).ConclusionsPoor diet and obesity are associate with severe BP, particularly among non-drinking older adults, suggesting targeted interventions in rural primary care.